Perancangan Dan Implementasi Aplikasi Pemesanan Makanan Berbasis Aplikasi Android - Bagus Aditya Abimanyu; Ari Syaripudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
The ordering system at Ayam Bakar Lamongan Cak Di still follows a conventional system, which involves contacting the restaurant owner, resulting in limited information regarding the menu and operating hours. Additionally, the ordering process for customers still adheres to a conventional system, leading to delays and inefficiencies in order management. To address these issues, the researchers developed a cashier, courier, and admin ordering application to facilitate an effective order processing system. This application aims to simplify the ordering process for customers, providing information on menus and facilitating food ordering. To integrate these ordering, cashier, courier, and admin applications, the researchers employed the API method as a connector. By utilizing API, these applications can seamlessly communicate and share data, ensuring more efficient integration. The development method chosen for the system is the agile method, coupled with UML architecture and MySQL database. Implementing the agile method involves several stages, including design, analysis, implementation, testing, documentation, deployment, and maintenance. This ensures that the creation of the Android-based food ordering application's information system allows for order placement, provides order status information, and indicates menu availability and operating hours.